Musée et troubles du spectre autistique - Cyrielle Leriche (Les Cahiers de l'École du Louvre)
Museum policy currently welcomes disabled visitors. However, one type of disability remains very marginalised in the museum world: autistic spectrum disorder. Autism is still somewhat of a mystery to the general public whose knowledge of it is too often rooted in commonplaces. The visits to cultural institutions by people with autism is strongly marked by this exclusion. The absence of autistic visitors from museums may be explained in many ways, particularly by an element characteristic of the museum: its sensorial environment. This study aims to demonstrate the impact of the sensorial environment of the museum on visitors with autism through a field study in order to propose an adaptation of the museum favourable to the visits of those with autism.